Doxorubicin-loaded nanoparticles for patients with advanced hepatocellular carcinoma after sorafenib treatment failure (RELIVE): a phase 3 randomised controlled trial. (June 2019) - Merle, Philippe; Blanc, Jean-Frederic; Phelip, Jean-Marc; Pelletier, Gilles; Bronowicki, Jean-Pierre; Touchefeu, Yann; Pageaux, Georges; Gerolami, René; Habersetzer, François; Nguyen-Khac, Eric; Casadei-Gardini, Andrea; Borbath, Ivan; et al.
Summary: Background: Cytotoxic chemotherapy is generally ineffective in patients with hepatocellular carcinoma. We assessed the intravenous perfusion of doxorubicin-loaded nanoparticles in patients with hepatocellular carcinoma in whom previous sorafenib therapy had failed. Methods: We did a multicentre, open-label, randomised, controlled phase 3 trial at 70 sites in 11 countries. Patients with hepatocellular carcinoma with one or more previous systemic therapies, including sorafenib, were randomly assigned to receive 30 mg/m 2 doxorubicin-loaded nanoparticles (30 mg/m 2 group), 20 mg/m 2 doxorubicin-loaded nanoparticles (20 mg/m 2 group), or standard care using a computer-generated randomisation list prepared by the funder and stratified by geographic region. Patients in the experimental groups received perfusion of the drug every 4 weeks and those in the control group received any systemic anticancer therapy (except sorafenib) as per investigator decision. The primary endpoint was overall survival in the intention-to-treat population. Safety was assessed in the population of patients who received at least one dose of their assigned treatment. This trial is registered with ClinicalTrials.gov, number NCT01655693 . Findings: Between June 15, 2012, and Jan 27, 2017, 541 patients were screened, of whom 144 were excluded and 397 were randomly assigned to one of the groups (133 to the 30 mg/m 2 group; 130 to the 20 mg/m 2 group; and 134 to the control group). Median follow-up was 22·7 months (IQR 11·2–34·9). After pooling the doxorubicin groups for the efficacy analysis, median overall survival was 9·1 months (95% CI 8·1–10·4) in the pooled doxorubicin-loaded nanoparticles group and 9·0 months (7·1–11·8) in the control group (HR 1·00 [95% CI 0·78–1·28], two-sided p=0·99). 227 (94%) of 242 patients who received doxorubicin-loaded nanoparticles and 100 (75%) of 134 patients in the control group had at least one treatment-emergent adverse event. The most common drug-related grade 3 or 4 treatment-emergent adverse events were neutropenia (25 [10%] of 242 treated with doxorubicin-loaded nanoparticles and eight [6%] of 134 in the control group), asthenia (six [2%] and four [3%]), and thrombocytopenia (three [1%] and ten [7%]). Six (2%) patients treated with doxorubicin-loaded nanoparticles and one (1%) of those in the control group were deemed by investigators to have had a drug-related death. Serious adverse events occurred in 74 (31%) patients who received doxorubicin-loaded nanoparticles and 48 (36%) in the control group. Interpretation: Doxorubicin-loaded nanoparticles did not improve overall survival for patients with hepatocellular carcinoma in whom previous sorafenib treatment had failed. Funding: Onxeo.